Development Tendencies of World Regions and Lithuanian Life Insurance Services Markets Under Globalization Conditions - Kindurys, Vytautas (Ekonomika, 2002)
Under existing conditions globalization of life insurance services markets has an influence to separate world regions life insurance markets development. The main peculiarity of present competition in life insurance markets of developed countries is sharpened competition for the leader position. In a lot of countries social maintenance changes, pension reform made more active life insurance. Strengthening of competition in insurance services markets determined origin of bank assurance, banks and life insurance companies integration. Globalization impact to world regions life insurance services markets determined foreign capital penetration to national markets, establishments of secondary enterprises. Lithuanian life insurance services market is small so far, but it has potential possibilities to grow in more rapid rates if there will be favourable exterior factors. Tendencies that are characteristic in Western countries markets lately became apparent also in Lithuanian life insurance services market development. Noteworthy tendencies are: comparatively intensive foreign capital penetration; life insurance companies and banks activity integration, development of oligopoly life insurance services market structure.